Study of fractional order Van der Pol equation - Mishra, V.; Das, S.; Jafari, H.; Ong, S.H. (Elsevier, 2015)
In this article, Homotopy analysis method is successfully used to find the approximate solution of fractional order Van der Pol equation. The fractional derivative is described in the Caputo sense.The numerical computations of convergence control parameters for the acceleration of convergence of approximate series solution are obtained by the analysis of minimization of error for different particular cases and the results are depicted through graphs. The salient feature of the article is the graphical presentation of achieving limit cycles for different parameters.
Keywords: Damping; Embedding parameter; Error analysis; Homotopy analysis method; Limit cycle; Oscillator equation